Supporting the parent‐to‐child transfer of self‐management responsibility for chronic kidney disease: A qualitative study - Ruth Nightingale; Sue Kirk; Veronica Swallow; Gretl A. McHugh (Wiley, 2023)
Abstract Introduction As children with long‐term conditions (LTCs) mature, they are usually expected to assume responsibility from their parents for self‐management of their condition. Little is known about what supports families with this handover of responsibility, including the role of healthcare professionals (HCPs). This study aimed to explore what supports young people with chronic kidney disease (CKD) to assume self‐management responsibility and parents to relinquish control. Methods A qualitative study, using a grounded theory approach was conducted. Individual and dyadic interviews and focus groups were carried out with 16 young people aged 13-17 years old with CKD, 13 parents, and 20 HCPs. Participants were recruited from two UK children's renal units. Findings Building and maintaining trust, fostering positivity, learning from mistakes, forming partnerships and individualized support, facilitated the transfer of self‐management responsibility. However, HCPs' focus on developing partnerships with young people meant some parents felt excluded, highlighting uncertainty around whether support should be child‐ or family‐centred. Although tailored support was identified as critical, aspects of local service provision appeared to impact on HCPs' capacity to implement individualized approaches. Conclusion This study has identified what supports the handover of responsibility, and, importantly, HCPs' current, and potential role in helping young people to assume responsibility for managing their LTC. Further research is needed to explore how HCPs' involvement balances child‐ and family‐centred care, and how HCPs can adopt personalized, strengths‐based approaches to help ensure the support that families receive is tailored to their individual needs. Patient or Public Contribution Patient and public involvement was integrated throughout the study, with young adults with CKD and parents who had a child with CKD actively involved in the study's design and delivery.